Ethnic Crossing Politics as a Political Strategy for the Winning Candidate Pair Radiapoh Hasiholan Sinaga & Zonny Waldi in the 2020 Simalungun Regent Election - Windawati Pinem (Universitas of Muhammadiyah Makassar, 2022)
This study aims to examine the political strategies used by Radiapoh Hasiholan Sinaga and Zonny Waldi in the election of candidates for the regent of Simalungun Regency in 2020. After the simultaneous and direct elections were held, political dynamics at the local level are still inseparable from ethnicity, religion, and kinship issues. This is what makes political competition in the region more heated. Therefore, a political strategy is needed, essential for political marketing. Radiapoh-Zonny's victory was inseparable from the political strategy used. Political strategy is formed from crucial issues in the Simalungun community, such as the plurality of tribes, religions, and groups. From these problems, a cross-ethnic political strategy was formed. Cross-ethnic politics is the election and incorporation of Simalungun regent candidates from various ethnic groups, religions, and races in the Simalungun Regency. The research method used is qualitative with literature study. Data collection techniques are carried out by collecting various literature such as research results, books, and journals. Data analysis was carried out using the triangulation method. This study shows that the issue of ethnicity has been successfully used as a political strategy not to divide society but rather as a political marketing strategy to attract voters' attention.Penelitian ini bertujuan untuk melihat strategi politik yang digunakan oleh Radiapoh Hasiholan Sinaga dan Zonny Waldi dalam pemilihan calon Bupati Kabupaten Simalungun tahun 2020. Pasca dilaksanakannya pilkada serentak dan langsung, dinamika politik di tingkat lokal masih belum terlepas dari persoalan etnisitas, keagamaan serta kekerabatan. Hal inilah yang menjadikan kompetisi politik di daerah semakin memanas. Oleh karena itu dibutuhkanlah sebuah strategi politik yang merupakan bagian penting dalam marketing politik. Kemenangan Radiapoh-Zonny tidak terlepas dari strategi politik yang digunakan. Strategi politik dibentuk dari isu-isu krusial yang ada dalam masyarakat Simalungun seperti kemajemukan suku, agama dan golongan. Dari persoalan tersebutlah strategi politik silang etnis terbentuk. Politik silang etnis adalah pemilihan dan penggabungan calon bupati Simalungun yang berasal dari berbagai suku, agama, dan ras yang ada di Kabupaten Simalungun. Adapun metode penelitian yang digunakan adalah kualitatif dengan studi pustaka. Teknik pengumpulan data dilakukan dengan mengumpulkan berbagai literatur seperti hasil penelitan, buku dan jurnal . Analisis data dilakukan dengan metode triangulasi.Adapun hasil dari penelitian ini bahwa isu etnisitas berhasil digunakan sebagai strategi politik bukan untuk memecah belah masyarakat, melainkan sebuah political marketing untuk menarik perhatian pemilih.